(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background and objectives: Worldwide annually, an estimated 5,15,000 women die of causes related to pregnancy and childbirth; of which 99% occur in developing countries. In developing regions of world Maternal Mortality Ratio (MMR) averages to 450 per lakh population (1). Pregnancy outcome is influenced by various maternal, socio-economic, cultural factors and also availability, accessibility of health care services (2). Most of our knowledge of factors affecting pregnancy outcome are derived from hospital based, cross-sectional studies which will have inherent biases. Hence this community based prospective study was intended to study the pregnancy outcome and its contributory factors both in rural area and urban slum to learn the differences in pregnancy outcome. Materials and methods: This community based prospective study was carried out among the antenatal mothers residing in the rural and urban field practice areas of Nathnagar, Bhagalpur from Feb 2020 to Feb 20121. Relevant information was collected using predesigned semi-structured questionnaire and antenatal examination. Conclusion: In our study major adverse pregnancy outcomes were low birth weight baby followed pre-term deliveries. Anemia, bad obstetric history, and duration of pregnancy were found to have a statistical significance influence on birth weight. There was no significant difference in pregnancy outcome between rural and urban slum.